Extension of the 5-alkynyluridine side chain via C–C-bond formation in modified organometallic nucleosides using the Nicholas reaction - Kaczmarek, Renata; Korczyński, Dariusz; Green, James R.; Dembinski, Roman (Beilstein Journal of Organic Chemistry, 2020)
Dicobalt hexacarbonyl nucleoside complexes of propargyl ether or esters of 5-substituted uridines react with diverse C-nucleophiles. Synthetic outcomes confirmed that the Nicholas reaction can be carried out in a nucleoside presence, leading to a divergent synthesis of novel metallo-nucleosides enriched with alkene, arene, arylketo, and heterocyclic functions, in the deoxy and ribo series.
Keywords: alkynes; 5-alkynyluridines; C–C-bond formation; dicobalt hexacarbonyl complexes; Nicholas reaction; nucleosides; propargyl cation

Modified Nucleosides in Biochemistry, Biotechnology and Medicine - Herdewijn, P. (Wiley-VCH, 2008)

Deoxynucleoside Analogs in Cancer Therapy - Godefridus, J. P. (Humana Press, 2006)

Chemical Synthesis of Nucleoside Analogues - Merino, P. (John Wiley & Sons, 2013)

(untitled) - Jordheim, L. P.; Durantel, D.; Zoulim, F.; Dumontet, C. (Nat. Rev. Drug Discovery, 2013)

(untitled) - Bobrovnikova-Marjon, E.; Hurov, J. B. (Annu. Rev. Med., 2014)

(untitled) - Kore, A. R.; Charles, I. (Curr. Org. Chem., 2012)

Palladium-Catalyzed Modification of Nucleosides, Nucleotides and Oligonucleotides - Kapdi, A. R.; Maiti, D.; Sanghvi, Y. S. (Elsevier, 2018)

(untitled) - Hilko, D. H.; Bornaghi, L. F.; Poulsen, S.-A. (J. Org. Chem., 2018)
See for a recent representative example of C-5 modified uridines.

(untitled) - Bag, S. S.; Gogoi, H. (J. Org. Chem., 2018)
See for a recent representative example of C-5 modified uridines.

(untitled) - Barthes, N. P. F.; Karpenko, I. A.; Dziuba, D.; Spadafora, M.; Auffret, J.; Demchenko, A. P.; Mély, Y.; Benhida, R.; Michel, B. Y.; Burger, A. (RSC Adv., 2015)
See for a ecent representative example of C-5 modified uridines.

(untitled) - Hottin, A.; Marx, A. (Acc. Chem. Res., 2016)

(untitled) - Mei, H.; Chaput, J. C. (Chem. Commun., 2018)

(untitled) - Sniady, A.; Durham, A.; Morreale, M. S.; Marcinek, A.; Szafert, S.; Lis, T.; Brzezinska, K. R.; Iwasaki, T.; Ohshima, T.; Mashima, K.; Dembinski, R. (J. Org. Chem., 2008)
and references cited therein.

(untitled) - Rao, M. S.; Esho, N.; Sergeant, C.; Dembinski, R. (J. Org. Chem., 2003)

(untitled) - Sniady, A.; Sevilla, M. D.; Meneni, S.; Lis, T.; Szafert, S.; Khanduri, D.; Finke, J. M.; Dembinski, R. (Chem. – Eur. J., 2009)

Metals in Medicine - Franz, K. J.; Metzler-Nolte, N. (Chem. Rev., 2019)

Bioorganometallic Chemistry: Applications in Drug Discovery, Biocatalysis, and Imaging - Jaouen, G.; Salmain, M. (John Wiley & Sons, 2015)

Concepts and Models in Bioinorganic Chemistry - Kraatz, H. B.; Metzler-Nolte, N. (Wiley-VCH, 2006)

Bioorganometallic Chemistry - Jaouen, G. (Wiley-VCH, 2006)

(untitled) - Gasser, G. (Chimia, 2015)

(untitled) - Gasser, G.; Ott, I.; Metzler-Nolte, N. (J. Med. Chem., 2011)

(untitled) - Timerbaev, A. R.; Hartinger, C. G.; Aleksenko, S. S.; Keppler, B. K. (Chem. Rev., 2006)

(untitled) - Hartinger, C. G.; Metzler-Nolte, N.; Dyson, P. J. (Organometallics, 2012)

(untitled) - Ott, I.; Gust, R. (Arch. Pharm. (Weinheim, Ger.), 2007)

(untitled) - Heffern, M. C.; Yamamoto, N.; Holbrook, R. J.; Eckermann, A. L.; Meade, T. J. (Curr. Opin. Chem. Biol., 2013)

(untitled) - Li, J.; Zhang, J.; Zhang, Q.; Wang, Y.; Bai, Z.; Zhao, Q.; He, D.; Wang, Z.; Zhang, J.; Chen, Y. (Bioorg. Med. Chem., 2019)
See for a recent representative example.

(untitled) - Berrino, E.; Milazzo, L.; Micheli, L.; Vullo, D.; Angeli, A.; Bozdag, M.; Nocentini, A.; Menicatti, M.; Bartolucci, G.; di Cesare Mannelli, L.; Ghelardini, C.; Supuran, C. T.; et al. (J. Med. Chem., 2019)

(untitled) - Atkin, A. J.; Williams, S.; Sawle, P.; Motterlini, R.; Lynam, J. M.; Fairlamb, I. J. S. (Dalton Trans., 2009)

(untitled) - Ott, I.; Kircher, B.; Dembinski, R.; Gust, R. (Expert Opin. Ther. Pat., 2008)

(untitled) - Munteanu, C. R.; Suntharalingam, K. (Dalton Trans., 2015)

(untitled) - Kaczmarek, R.; Korczyński, D.; Królewska-Golińska, K.; Wheeler, K. A.; Chavez, F. A.; Mikus, A.; Dembinski, R. (ChemistryOpen, 2018)
and references cited therein.

(untitled) - Sergeant, C. D.; Ott, I.; Sniady, A.; Meneni, S.; Gust, R.; Rheingold, A. L.; Dembinski, R. (Org. Biomol. Chem., 2008)

(untitled) - Meneni, S.; Ott, I.; Sergeant, C. D.; Sniady, A.; Gust, R.; Dembinski, R. (Bioorg. Med. Chem., 2007)
See for anticancer activity of precursors 5-alkynyl 2'-deoxyuridines.

(untitled) - Kann, N. (Curr. Org. Chem., 2012)

Name Reactions for Homologations, Part 1 - Shea, K. M. (Nicholas Reaction, 2009)

(untitled) - Díaz, D. D.; Betancort, J. M.; Martín, V. S. (Synlett, 2007)

(untitled) - Teobald, B. J. (Tetrahedron, 2002)

(untitled) - Green, J. R. (Curr. Org. Chem., 2001)

Comprehensive Organometallic Chemistry II - Caffyn, A. J. M.; Nicholas, K. M. (Transition Metal Alkyne Complexes: Transition Metal-stabilized Propargyl Systems, 1995)

(untitled) - Green, J. R.; Nicholas, K. M. (Org. React.)

(untitled) - Roth, K.-D. (Synlett, 1993)

(untitled) - Taj, R. A.; Green, J. R. (J. Org. Chem., 2010)

(untitled) - Krafft, M. E.; Cheung, Y. Y.; Wright, C.; Cali, R. (J. Org. Chem., 1996)

(untitled) - O'Boyle, J. E.; Nicholas, K. M. (Tetrahedron Lett., 1980)

(untitled) - Takano, S.; Sugihara, T.; Ogasawara, K. (Synlett, 1992)

(untitled) - Green, J. R. (Chem. Commun., 1998)

(untitled) - Nicholas, K. M.; Mulvaney, M.; Bayer, M. (J. Am. Chem. Soc., 1980)

(untitled) - Tanino, K.; Shimizu, T.; Miyama, M.; Kuwajima, I. (J. Am. Chem. Soc., 2000)

(untitled) - St Onge, B.; Green, J. R. (Synlett, 2017)

(untitled) - Green, J. R. (Eur. J. Org. Chem., 2008)

(untitled) - Isobe, M.; Hamajima, A. (Nat. Prod. Rep., 2010)

(untitled) - Hernández, J. N.; Ramírez, M. A.; Rodríguez, M. L.; Martín, V. S. (Org. Lett., 2008)

(untitled) - Miyazaki, A.; Asanuma, M.; Dodo, K.; Egami, H.; Sodeoka, M. (Chem. – Eur. J., 2014)

(untitled) - Prasad, J. S.; Liebeskind, L. S. (Tetrahedron Lett., 1987)

(untitled) - Gruselle, M.; Cordier, C.; Salmain, M.; El Amouri, H.; Guerin, C.; Vaissermann, J.; Jaouen, G. (Organometallics, 1990)
See for a representative example.

(untitled) - Tanaka, S.; Isobe, M. (Tetrahedron, 1994)

(untitled) - Jiang, Y.; Isobe, M. (Tetrahedron, 1996)

(untitled) - Mukai, C.; Itoh, T.; Hanaoka, M. (Tetrahedron Lett., 1997)

(untitled) - Hosokawa, S.; Isobe, M. (J. Org. Chem., 1999)

(untitled) - Gómez, A. M.; Uriel, C.; Valverde, S.; López, J. C. (Org. Lett., 2006)

(untitled) - Lobo, F.; Gómez, A. M.; Miranda, S.; López, J. C. (Chem. – Eur. J., 2014)

(untitled) - Bag, S. S.; Das, S. K. (Tetrahedron, 2019)

(untitled) - Esho, N.; Davies, B.; Lee, J.; Dembinski, R. (Chem. Commun., 2002)

(untitled) - Yamamoto, Y.; Seko, T.; Nakamura, H.; Nemoto, H. (Heteroat. Chem., 1992)
To our knowledge, compounds 2 and 3 have not yet been reported. See for a related protected compound.

(untitled) - Tolstikov, V. V.; Stetsenko, D. A.; Potapov, V. K.; Sverdlov, E. D. (Nucleosides Nucleotides, 1997)
See for a related protected compound.